First record of Petrorhagia dubia (Raf.) G. López & Romo (Caryophyllaceae) in Lombardy - Quaglini, Lara A.; Galasso, Gabriele (Natural History Sciences, 2025)
During floristic surveys conducted between May and June 2025 at the former industrial area of La Goccia, in the Bovisa district of Milan, a naturalized population of Petrorhagia dubia was discovered, a plant previously unreported for Lombardy. The species, native to the Mediterranean region and introduced in several continents, was found in ephemeral grasslands at the edges of abandoned paved areas. The species is described in detail, with particular focus on the features that distinguish it from P. prolifera, a very common species in Lombardy with which it can easily be confused. This finding contributes to improving knowledge of the urban flora of Milan.
Keywords: Milan; secondary distribution; urban flora